Question

# In $$\triangle ABC$$ and $$\triangle XYZ$$, if $$\angle A$$ and $$\angle X$$ are acute angles such that $$\cos { A } =\cos { x }$$ then show that $$\angle A=\angle X$$.

Solution

## GIven, for $$\triangle ABC$$ and $$\triangle XYZ$$$$\angle A$$ and $$\angle X$$ are acute trianlgeWhere $$\cos A=\cos X$$Also given, to show that $$\angle A=\angle X$$$$\because\cos=\dfrac{length\ of\ adj\ side}{length\ of\ hypotenuse}$$$$\Rightarrow \dfrac{AB}{AC}=\dfrac{XY}{XZ}$$Let $$\dfrac{AB}{AC}=\dfrac{XY}{XZ}=k$$   [where $$k$$ is a constant]So we get, $$\dfrac{AB}{XY}=\dfrac{AC}{XZ}=k\rightarrow eq (1)$$taking then separately we get, $$\dfrac{AB}{XY}=k\Rightarrow AB=k\times y$$, parallel $$\dfrac{AC}{XZ}=k\Rightarrow AC=kXZ$$now let us consider both the triangles opposite sides with their distance $$\sqrt{x_{2}^{2}-x_{1}^{2}}=d$$ we get, $$\dfrac{BC}{ZY}=\dfrac{\sqrt{AC^{2}-AB^{2}}}{\sqrt{XZ^{2}-XY^{2}}}$$      [from eqb (1) & eqn (2) we get $$AB=KXY, AC=KXZ$$]by substituting the values we get$$\dfrac{BC}{ZY}=k\dfrac{\sqrt{XZ^{2}-XY^{2}}}{\sqrt{XZ^{2}-XY^{2}}}\Rightarrow \dfrac{\sqrt{k^{2}}[\sqrt{XZ^{2}-XY^{2}}]}{\sqrt{XZ^{2}-XY^{2}}}$$$$\Rightarrow \dfrac{BC}{ZY}=k\dfrac{\sqrt{XZ^{2}-XY^{2}}}{\sqrt{XZ^{2}-XY^{2}}}\Leftrightarrow \dfrac{BC}{XY}=k$$[Let us now substitute $$k$$ in eq $$(1)$$]$$\Rightarrow \dfrac{AB}{XY}=\dfrac{AC}{XZ}=\dfrac{BC}{ZY}$$$$\therefore$$ By $$SSS$$ similarity we get $$\triangle ABC\sim \triangle XYZ$$$$\therefore$$ By property of similarity $$\angle A =\angle X$$Mathematics

Suggest Corrections

0

Similar questions
View More

People also searched for
View More